PERANCANGAN KAMPANYE UNTUK MENGENALKAN DAN MENYEMBUHKAN LUKA BATIN BAGI GEN Z - Liem Abigail Indira Salim; Elisabeth Christine Yuwono; Vanessa Yusuf (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2026)
A person's actions and behavior are often rooted in past life experiences. Emotional wounds or trauma experienced during childhood can leave lasting impacts into adulthood and potentially cause negative effects. This campaign is designed to support the audience in confronting and healing their inner wounds, to prevent these wounds from negatively affecting themselves, others, or future generations. The campaign is carried out online through social media platforms such as TikTok and Instagram, and is complemented by offline activities and the use of merchandise media. The campaign planning adopts a qualitative approach through interviews, questionnaires, and observations. The proposed solution is the Healin’Me campaign, with the tagline “Healing The Inner Child in Me”. This campaign aims to help the audience recognize the root causes and impacts of emotional wounds, while also learning how to accept and heal them so they are not passed down emotionally. In addition, the campaign provides a safe space for the audience to share their stories, build empathy, and foster mutual support in the healing journey